12 hour shift [videorecording (DVD)] - Grant, Brea; Arquette, David; Bettis, Angela; Farnworth, Chloe; Gamby-Turner, Nikea; Williamson, Kit, 1985-; Foley, Mick (Magnolia Home Entertainment, 2021)
It's 1999 and throughout one twelve-hour shift at an Arkansas hospital, a junkie nurse, her scheming cousin, and a group of black market organ-trading criminals start a heist that could lead to their imminent demises.